New Molecular Data in the Truffle-like Fungus, Aroramyces herrerae, Reveal a Novel Cryptic Ancestral Taxon, Pterosporomyces herrerae gen. nov. (Global Journal of Science Frontier Research, 2021)
Recently, Aroramyces herrerae was described based on morphology, ecology, and taxonomically placed in the family Hysterangiaceae (Hysterangiales). However, a DNA analysis revealed that A. herrerae belongs to a new sequestrate cryptic genus, Pterosporomyces, in the family Trappeaceae (Phallales), nested with Restingomyces reticulatus and Phalobata alba and jointly forming a basal clade of Phallales with strong statistical support. Pterosporomyces herrerae gen. nov
Keywords: fungi evolution; truffle; angiocarpic fungi; hypogeous fungi